Epic Singers and Oral Tradition - Lord, Albert Bates (Book collections on Project MUSE., 1991)
Albert Bates Lord here offers an unparalleled overview of the nature of oral-traditional epic songs and the practices of the singers who composed them. Shaped by the conviction that theory should be based on what singers actually do, and have done in times past, the essays collected here span half a century of Lord's research on the oral tradition from Homer to the twentieth century. Drawing on his extensive fieldwork in living oral traditions and on the theoretical writings of Milman Parry, Lord concentrates on the singers and their art as manifested in texts of performance. In thirteen essays, some previously unpublished and all of them revised for book publication, he explores questions of composition, transmittal, and interpretation and raises important comparative issues. Individual chapters discuss aspects of the Homeric poems, South Slavic oral-traditional epics, the songs of Avdo Metedovic, Beowulf and Anglo-Saxon poetry, the medieval Greek Digenis Akritas and other medieval epics, central Asiatic and Balkan epics, the Finnish Kalevala, and the Bulgarian oral epic. The work of one of the most respected scholars of his generation, Epic Singers and Oral Tradition will be an invaluable resource for scholars and students of myth and folklore, classicists, medievalists, Slavists, comparatists, literary theorists, and anthropologists.